L'autorisation d'exercer le recours collectif - Bouchard, Mario (Les Cahiers de droit, 1980)
This paper is basically an analysis of art. 1003 of the Code of Civil Procedure of Québec. Following a brief survey of the origins of class actions in English and American law, the Québec class action is defined as a form of procedure available to plaintiffs only, based on the existence of a group acting through a representative. It is then distinguished from similar forms of procedure, whether under Québec law (art. 59 and 67 C.C.P.) or foreign law (constitution de partie civile, relator, Adhasionsprozess, etc.). The introductory part goes on to examine the relationship of class actions to basic principles of civil procedure in Québec (such as the rules on standing), to challenge some widely-held beliefs concerning class actions and their social and economic impact, and finally to underline the unitary character of class actions under Québec law. Brought under closer analysis, the introductory paragraph of art. 1003 underscores the requirement of a hearing by the court, indicates the nature and timing of judicial authorization, and determines the scope and extent of the conferment of representative status. The case of groups referred to in art. 1048 C.C.P. is examined in this connection. The paper then surveys in turn each of the lettered paragraphs of art. 1003 C.C.P., in the light of similar provisions in Québec and other jurisdictions, with special reference to the American Federal rule. Similitudes and contrasts are thereby brought into view. It thus appears that paragraph d) is alone in showing definite American influence; indeed, discussion of this paragraph centres on foreign law. A critical review is made of the cases under each of the paragraphs. Certain approaches to the construction of art. 1003 are also criticized, especially those implying further conditions to the grant of representative status or involving the use or irrelevant tests in this regard, in spite of differences between American and Québec procedures or between the American and Canadian constitutions. Finally, the paper underlines the requirement, imposed by art. 1022 and 1024 C.C.P., that conditions laid down by art. 1003 continue to exist throughout the duration of the case. The paper concludes that the Québec class action is probably the most liberal of all, and may open up new approaches toward using court proceedings to implement policy. However, it is feared that the courts may prove unreceptive to the innovative spirit behind this form of action; indeed, some cases decided so far seem to show a serious misapprehension of its character.